1981
DOI: 10.1111/j.1651-2227.1981.tb06238.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Apoprotein and Lipid Patterns in Newborns: Influence of Nutritional Factors

Abstract: In this study the plasma lipid and apoprotein concentrations have been assayed in 80 full-term newborns, at 0, 7 and 30 days of life, and the data have been analyzed as a function of the composition of the diet. The total cholesterol, HDL cholesterol, the apo A-I, A-II and B protein concentrations were followed in 4 groups of infants receiving respectively breast-feeding, adapted formulae I, II with a P/S ratio close to that of maternal milk and a formula III enriched with polyunsaturated fatty acids. After 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
2

Year Published

1983
1983
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 12 publications
5
19
2
Order By: Relevance
“…Various studies have shown that diet affects the Apo B or LDL-cholesterol levels in older infants (8,18,27), but our data and that of Lane and McConathy (13) establish that in 3-to 5-day-old neonates whether the infant is breast-fed, formula-fed, or breast-fed with formula complement does not significantly influence Apo B levels. It has been well documented that certain perinatal factors do influence lipid levels (4, 5, 8, 9, 22).…”
Section: Diet and Other Variablescontrasting
confidence: 39%
“…Various studies have shown that diet affects the Apo B or LDL-cholesterol levels in older infants (8,18,27), but our data and that of Lane and McConathy (13) establish that in 3-to 5-day-old neonates whether the infant is breast-fed, formula-fed, or breast-fed with formula complement does not significantly influence Apo B levels. It has been well documented that certain perinatal factors do influence lipid levels (4, 5, 8, 9, 22).…”
Section: Diet and Other Variablescontrasting
confidence: 39%
“…Cord-serum lipoproteins in our infants were as in normal term infants (36)(37)(38)(39)(40). In addition, cord-serum lipoproteins and apolipoproteins were similar in all three groups, although infants born to diabetic mothers have been reported to have higher cholesterol and lower triglyceride levels than normal term infants (41,42).…”
Section: Discussionmentioning
confidence: 53%
“…We have applied this procedure to the quantitation of the lipoprotein profiles in newborns at 0, 7 and 30 days in order to obtain the compositional analysis of the various lipoprotein fractions. As previously shown (17,18) the lipoprotein patterns in newborns are profoundly modified during the first month of life when several synthetic and catabolic pathways are developing.…”
mentioning
confidence: 63%